Influence of socioeconomic factors on litigation in surgery: Addressing the gap in malpractice literature. Issue 2 (February 2020) - Kearney, L.; Concannon, E.; Rolle, C.; Hynes, M.; Malesevic, V.; Kelly, J.L.
Summary: The practice of medicine is occasionally volatile and increasingly litigious. Within the specialities, plastic surgery has a high risk, with negative outcomes seen as dissatisfaction, as compared to actual physical harm. To date, most research has focused on potential triggers for litigation, such as poor communication and perceived behavioural deficiencies among physicians. Few studies have addressed patient characteristics or socioeconomic factors. The 'Influence of Socio-Economic Factors on Attitudes Towards Surgery' questionnaire was designed to reflect these goals. It was distributed for a 12-month period to patients in an Emergency Department waiting room. Three hundred twelve completed questionnaires were submitted for analysis. Within the study population, we identified certain socioeconomic trends among those with a low threshold to pursue litigation. Patients with a low threshold to sue were more likely to be male, aged 25–55 years, currently unemployed, without dependents and divorced. However, these parameters did not reach statistical significance. Although these characteristics are interesting, they cannot reliably identify or predict those with a low threshold for litigation. For now, the clinical focus should remain on careful adherence to best practice in an effort to reduce the risk of potential litigation.